1976
DOI: 10.1136/gut.17.12.1001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraluminal oxygen on experimental ischaemia of the intestine.

Abstract: SUMMARY The small bowel of 44 rats has been made ischaemic for 120 minutes by occluding the superior mesenteric artery. Gaseous oxygen was introduced into the small bowel lumen of 18 of the rats, and gaseous nitrogen into the bowel lumen of a further eight, 30 minutes after the start of the ischaemia. The mortality rate of thecontrolgroup of 18 rats was 89 %, significantlyhigher than the 39 % mortality of the oxygen-treated rats (p < 0 005). None of the eight rats treated with intraluminal nitrogen survived. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

1977
1977
2006
2006

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…Shute [18] demonstrated in rats that 100% oxygen introduced into the gut lumen during superior mesenteric artery occlusion reduced mortality, and histological evidence of intestinal ischemia was also diminished.…”
Section: Discussionmentioning
confidence: 97%
“…Shute [18] demonstrated in rats that 100% oxygen introduced into the gut lumen during superior mesenteric artery occlusion reduced mortality, and histological evidence of intestinal ischemia was also diminished.…”
Section: Discussionmentioning
confidence: 97%
“…The former explanation is unlikely in view of the relatively short period of exposure of the anaerobes to oxygen, and because death of these organisms would, in the short term, lead to the release of large quantities of endotoxin. A much more likely explanation is that the decreased absorption of endotoxin from the bowel lumen is due to previously described maintenance of the mucosal 'barrier' by intraluminal oxygen (Shute 1975).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in mortality resulting from the introduction of oxygen into the bowel lumen of rats subjected to superior mesenteric artery occlusion has been described previously (Shute, 1975). In that study two identical groups of rats were subjected to occlusion of the superior mesenteric artery (SMA) under general anaesthetic.…”
mentioning
confidence: 93%
“…The proposed mechanisms of the beneficial effects of HBO therapy are 1) inhibition of expressing adhesion molecules and migration of neutrophils in the acute injury phase (6,7), and 2) increased oxygen availability in tissue caused by increased blood oxygen tension and increased distance of interstitial oxygen diffusion. In other studies, intraluminal administration of either oxygen or O 2 -PFC preserves intestinal mucosa against I/R injury (3,4). However, administration of those substances in gut lumen is technically difficult or even harmful in certain clinical situations.…”
Section: Introductionmentioning
confidence: 98%
“…Because many investigators considered derangement of the gut mucosal barrier function important in the pathogenesis of septic shock and multiple organ dysfunction syndrome (MODS), it is important to develop therapeutic modalities to preserve gut mucosa and prevent barrier dysfunction. Previous studies demonstrated that intraluminal administration of either oxygen or oxygenated perfluorochemical (O 2 -PFC) preserves intestinal mucosa against ischemia/reperfusion (I/R) injury (3,4). Hyperbaric oxygen therapy was also demonstrated to effectively preserve gut barrier function in shock and sepsis models (5,6).…”
Section: Introductionmentioning
confidence: 99%